Molecular imprinting sensor based on zeolitic imidazolate framework derived Co, N-doped carbon loaded on reduced graphene oxide toward the determination of dopamine - Ren, Shufang; Liu, Xiaohang; Liu, Yahui; Zhao, Junpeng; Zhang, Yuan; Zheng, Zhixiang (Mikrochimica acta (1966), 2024)
A novel voltammetric sensor designed for dopamine (DA) detection is presented utilizing a combination of zeolitic imidazolate framework (ZIF-67) derived cobalt and nitrogen-doped carbon on reduced graphene oxide (Co–N-C/rGO). ZIF-67 cubic crystals were synthesized in situ and deposited onto the graphene oxide (GO) surface through room-temperature reactions. High-temperature calcination resulted in partially collapsed cubic and spherical carbon, while simultaneously reducing GO to rGO. A molecular imprinting resorcinol polymer (MIP) membrane was also in situ applied to the Co–N-C/rGO/glassy carbon electrode (GCE) via electropolymerization. Analyses using cyclic voltammetry, electrochemical impedance, and pulse voltammetry reveal that the modified MIP/Co–N-C/rGO/GCE electrodes show improved electroconductivity and notable electrochemical reactivity towards dopamine. After optimizing detection parameters, the sensor demonstrates a wide linear detection range of 0.01—0.5 and 0.5—100 μmol/L, with a limit of detection (LOD) of 3.33 nmol/L (S/N = 3). Additionally, the sensor displays strong robustness, including excellent selectivity, significant resistance to interference, and long-term stability. It also shows satisfactory recovery in detecting spiked real samples. Graphical Abstract